Bactericidal and Hemolytic Activities of Synthetic Peptides Derived from Granulysin - Siano, Alvaro Sebastían (2010)
Granulysin is a human polypeptide produced by cytolytic cells active against a broad range of microbes. Three peptides covering the regions 25-50 (Gr-1 and Gr-2) and 39-62 (Gr-3) of granulysin were synthesized, and their in vitro activity against Mycobacterium tuberculosis was evaluated. The most active peptide was Gr-1C, containing a disulphide bridge, with Minimal Inhibitory Concentration value of 10.1 μM. In concentrations of up to 50 μM, Gr-1 and Gr2 didn't exceed 30% of hemolysis.